Gesto e captura do instante poético: Haicais em Língua de Sinais - Oliveira, Carmen Elisabete de (2025)
This thesis aims to explore and deepen studies on Literature in Libras, with an emphasis on the literary genre haiku, which is still little known and produced by Brazilian deaf people. Haiku is a poetic form created in the 16th century and is characterized by being a concise and objective poem. In its early days, it was composed with themes related to everyday life and nature. Over time, haiku writers began to explore a variety of themes, including the feelings of the lyrical self and social issues, employing a great poetic and imagery load. The objective of this thesis is to demonstrate that deaf readers can be poetically sensitized to create their own haikus and express them through Brazilian Sign Language (Libras), in addition to recording them through videos, exploring the linguistic and aesthetic resources that this language offers. In addition, this proposal highlights the role of the mediating teacher in literary reading with deaf people, aiming to enhance the experience of reading these poems. This approach is based on Literature Studies, which emphasize identity issues from perspectives that border languages, cultures and interarts. This study sought to answer the following questions: “Is it possible to poetically sensitize deaf people through the creation, expression and recording of haikus in Libras?” "Haiku in Sign Language has characteristics intrinsic to this language, so is it possible to outline a concept of haiku appropriate to this modality?". According to Sutton-Spence (2021), haiku in Sign Language combines and adapts the original elements of the Japanese literary genre. The author highlights that although there is still no formal definition for this style, there are descriptions of the characteristics of these poems, which are linked to the language. This is because these literary productions are written in a spatial-kinesthetic language. Researcher Kaneko (2008) also emphasizes that more research on these poems is needed in order to outline a concept. In this study, I propose a concept for this form of haiku, based on researchers such as Kaneko (2008) and Sutton-Spence (2021), who explored this genre in Sign Languages. Furthermore, the methodology in a qualitative action research approach and Ethnolibras allowed the application of literary aesthetic experiences developed in Extension Courses in Literature in Libras, with a focus on haikus. In the courses, I followed the creative process of approximately thirty-four deaf people, from the production to the recording of poems in Libras, which were later documented through SignWriting by a deaf teacher. To support the discussions and analyses, this research is anchored in theories and authors who discuss concepts of Haiku, such as Francheti (2008), Donizeti (2009), Leminski and Pires (1990); and, of haiku in Sign Language, such as Kaneko (2008) and Sutton- Spence (2014; 2021). The reading mediation work carried out in the extension course modules was based on the reflections of Candido (1989), Lajolo (1986), Zilberman (1988; 2008), Aguiar and Bordini (1993) and Cosson (2007), who defend literature as a fundamental human right. Based on the results achieved, the research confirmed that deaf people can be poetically sensitized through the creation of haikus, and highlights the importance of providing literary access through Libras. The collection of forty haikus, created with great creativity by the course participants, not only enriches the literary and cultural heritage of the deaf community, but also serves as an important resource for raising literary awareness and promoting literature in Libras. To expand the reach of this work, the haikus in Libras and SignWriting will be made available on the YouTube platform, on the channel of the Distance Education Center of the State University of Western Paraná - NEaDUNI and on the channel of the Center for Comparative Studies and Research in Literature, Culture, History and Memory in Latin America - NuECP, providing an accessible experience to all those interested in this poetic form. Thus, this thesis contributes significantly to the appreciation of poetry in Sign Languages, to the literary literacy of the deaf and to cultural inclusion.